Psychological health of Indian youth during COVID-19: a study through three chronological surveys - Babita Goyal; Alka Sabharwal; Vibha Chauhan; Lalit Mohan Joshi (Intelektual Pustaka Media Utama, 2023)
The COVID-19 pandemic and its aftereffects have affected human lives psychologically, economically, and socially. The study examines the dynamics of mental health problems faced by young adults and the consequent effects on their daily lives during the pandemic period. Three surveys were conducted among colleges/universities going students in India during the time periods May-June 2020, October 2020-February 2021, and January-February 2022; using Strengths and Difficulties Questionnaire (SDQ) 17+ self-reported extended version. Through 1,021, 743, and 932 responses in the three surveys respectively, the effect of the pandemic on the mental health (characterized by behavioral problems and social dysfunction) of respondents, categorized on basis of demographic variables and ‘COVID-19’ status was studied. Females were found to be more ‘distressed’ than during this period. There was no effect of age and family income. The 45% of the respondents in the Non-COVID group and 48% in the COVID-19 group had severe distress. With the passing of time, both the number of problem areas and the severity of problems faced by young adults increased thus affecting their day-to-day activities. The proportions of the respondents in borderline and abnormal categories were much higher both for difficulty and the impact scores of SDQ than the standard proportions.